IMPLEMENTASI PERLINDUNGAN HUKUM ATAS KESELAMATAN KERJA PADA PERUSAHAAN JASA KONSTRUKSI (STUDI DI PT. SASMITO) - Hartanto, Rony; Puspitosari, Hervina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Occupational safety is the rights of citizens based on article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Based on the Manpower Law, workers/laborers have the right to occupational protection and safety. This research is to find out how the implementation of legal protection for work safety in the construction service company PT Sasmito. This study uses empirical juridical research methods. Collecting data by means of interviews and literature study, using descriptive analytical methods and using a qualitative approach. Research results in the form of PT. Sasmito in protecting work safety, namely forming policies in the form of OSH planning, implementing OSH plans, monitoring and evaluating OSH work, reviewing and improving SMK3 performance, PT. Sasmito also participated in the workers' social security program. PT. Sasmito applies OHSAS 18001:2015 certification, conducts investigations, makes efforts related to victims, and performs managing control. PT. Sasmito experienced obstacles which were obstacles such as obstacles in protecting work safety due to low awareness of workers and the many laws and regulations related to K3, then when a work accident occurred in the form of a lack of supporting tools etc. and after a work accident, namely loss of workers and a limit on BPJS. From these various obstacles PT. Sasmito made an effort by conducting K3 socialization and imposing fines on workers who did not comply with PT. Sasmito